Who benefits from IPO underpricing? Evidence form hybrid bookbuilding offerings - Vicente Pons-Sanz (European Central Bank (ECB), 2005)
This paper uses a unique sample of 175 Spanish equity offerings from 1985 to 2002 to test who benefits from IPO underpricing and why. Institutions receive nearly 75% of the profits in underpriced issues, while they have to bear only 56% of the losses in overpriced offerings. Superior information regarding first day underpricing cannot completely explain the institutional abnormal profits. Underwriters are better informed about the companies they take public, and use that information to favor their long term clients. The preferential treatment of institutional investors, however, does not come at the expense of retail investors. Retail investors earn positive profits from participating in the new issues market. The driving factor behind the relative retail large allocation in overpriced issues when compared to underpriced offerings is not the underwriter allocation bias in favor of institutional investors. Retail investors subscribe more heavily to underpriced issues, consistent with individuals being partially informed.
Keywords: G32; G24; 330; Allocations; Initial Public Offerings; Retail Investors; Winner's Curse; Börsengang; Preismanagement; Börsenkurs; Spanien